1986
DOI: 10.1901/jaba.1986.19-381
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Fading and Transfer in the Treatment of Self‐restraint and Self‐injurious Behavior

Abstract: We conducted several manipulations of mechanical restraint properties during the course of treatment for two profoundly retarded adolescents who exhibited both self-restraint and self-injurious behavior. In study 1, a combination of prompting, differential reinforcement, and stimulus fading reduced one subject's self-restraint, which consisted of holding rigid tubes on his arms. Subsequently, stimulus control of both self-restraint and self-injurious behavior was transferred to tennis wrist bands. In study 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 22 publications
3
23
2
Order By: Relevance
“…1992). Others have considered self‐restraint and SIB to be members of the same response class (Pace et al . 1986), or to be functionally independent responses (Smith et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1992). Others have considered self‐restraint and SIB to be members of the same response class (Pace et al . 1986), or to be functionally independent responses (Smith et al .…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have suggested that SIB and self‐restraint may be maintained by the same environmental events. For example, Pace et al . (1986) found that both self‐restraint and SIB shown by two individuals was maintained by escape from demands.…”
Section: Introductionmentioning
confidence: 96%
“…This approach was not taken in the present study because, in three of the four cases in which SIBIS was continued after formal data collection, there was no desire on the part ofparents or guardians to eliminate SIBIS. Other approaches that might be considered indude use of the SIBIS remote and stimulus fading, which has been used with other forms of mechanical restraints (Pace, Iwata, Edwards, & McCosh, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…In other cases, it may be possible to gradually shape the form of self-restraint into one which is less restrictive and socially stigmatizing. Pace, Iwata, Edwards, and McCosh (1986) progessively modified self-restraint involving wearing rigid tubes on the arms to wearing of tennis wrist bands while maintaining low levels of SIB. However, additional intervention including shaping and reinforcement of behaviours involving removal of hands from restraint may also be necessary (Lerman, Iwata, Smith, & Vollmer, 1994).…”
Section: Treatment Of Self-restraintmentioning
confidence: 99%